TRANSFORMATION OF HOME-BASED TRADITIONAL JAMU MARKETING FROM CONVENTIONAL TO ONLINE SYSTEMS WITHIN THE MSME MARKET - Sugara, Asep; Mutharom, Mutharom; Astuti, Aie (STAI Darul Qalam Tangerang, 2023)
This study aims to explain the process of transforming the business of selling processed herbal medicine from a conventional system to an online system and to explain the opportunities and challenges of this business going forward. The research method in writing this thesis is descriptive and uses 5 key informants as traditional herbal medicine business actors, herbs and pharmacies. The increasing consumption of herbal medicine by the community is influenced by various factors, such as personal factors, marketing factors, socio-cultural factors, psychological factors and price factors. These various factors have an impact on the level of consumer/customer acceptance of herbal medicine from conventional trading businesses to online trading businesses. The determining factor in the process of converting a conventional herbal medicine business into an online herbal medicine trading business is the legality factor in the circulation and use of herbal medicine . It is necessary to conduct further investigations regarding alternative traditional herbal medicine, the availability of herbal basic ingredients / herbal raw materials so that the herbal medicine manufacturing process can continue